Challenges and Opportunities for Sustainable Development in Uzbekistan’s Agroeconomy - R. B. , Asamov.; Y. B. , Yusupov (American Journal of Biology and Natural Sciences, 2025)
Agricultural economics (agroeconomy) represents a crucial pillar of sustainable development, as it links food security, resource management, and economic growth. In the modern era, rising population, climate change, and market volatility have created new challenges for agricultural producers worldwide. Uzbekistan and other Central Asian countries, where agriculture remains a dominant sector, face particular constraints related to water scarcity, outdated farming practices, and weak integration into global markets. This paper explores the significance of agroeconomy in ensuring food security and rural livelihoods, evaluates major constraints, and highlights pathways for sustainable growth through innovation, institutional reforms, and global trade integration. The findings emphasize that agroeconomy is not only about agricultural productivity but also about developing resilient systems that can adapt to environmental, social, and economic transformations.